AIRFIELD LIGHTING VIRTUAL REALITY FOR EDUCATION IN MAKASSAR AVIATION POLYTECHNIC - PURBO WARTOYO, BAYU; Yahya, Muhammad; Syafar, A. Muhammad; Agung, Muhammad (Pascasarjana Universitas Negeri Makassar, 2024)
Airport Technology encompasses learning outcomes including Airport Mechanical Technician, Building and Foundation Technician, and Airport Electrical Technician. Graduates are expected to operate and maintain electrical, mechanical, building, and runway equipment in accordance with standard operational procedures and applicable regulations, particularly mastering the Airfield Lighting System (ALS). This study was conducted at Makassar Aviation Polytechnic in 2023, utilizing a Likert scale to assess student satisfaction regarding the use of virtual reality devices for ALS. The assessment results indicated that the Application and Device indicators received a score of 409 out of 480, Appearance scored 412 out of 480, Language achieved 296 out of 360, Content received 694 out of 840, and Usage scored 885 out of 1080. All indicators demonstrated a calculated r value greater than 0.388. In conclusion, the application of virtual reality technology in airfield lighting is highly conducive to education and training, enhancing skills in this area.